Do Economic Theories Inform Policy?: Analysis of the influence of the Chicago School on European Union competition policy - Dzmitry Bartalevich (Copenhagen Business School (CBS), 2017)
Adopting the (institutionalist) premise that ideas and the economic theories within which they are embedded influence policy, the dissertation investigates the influence of the Chicago School of antitrust analysis on the competition policy of the European Union (EU). The dissertation encapsulates three articles. The first article employs qualitative content analysis to assess whether and the extent to which the European Commission incorporates Chicago School theory into EU competition policy. It does so on the basis of current Commission Guidelines, Notices, and Block Exemption Regulations that address EU antitrust rules and EU merger control. The second article is exploratory; it narrows the focus on EU merger control and employs descriptive network analysis to investigate the overall composition of mergers cleared by the Commission during the period 2004– 2015 and attempts to reinforce the results of the analysis in the first article. The third article expands on the findings of the first and second articles and employs inferential network analysis with exponential random graph models to analyze, on the basis of Commission merger cases cleared during the period 2004–2015, whether the Harvard School, the Freiburg School, and considerations for Single Market integration underpin EU merger control, in addition to the influence of the Chicago School. The analysis presented in the articles suggests that the Chicago School has exerted considerable influence over EU competition policy. The findings further indicate that there is a strong presence of financial institutions among merger and acquisition transactions with an EU dimension in EU merger control. Finally, the findings show that the Commission appears to have a particular approach to EU competition policy that, despite being influenced by the Chicago School, cannot be explained entirely by it.
hdl:10398/9530
Keywords: 650